Improving Students’ Writing Skill Through Creative Writing at English Study Program IAIN Fattahul Muluk Papua - Erfin Wijayanti (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
The goals of this research are to find out the application of Creative Writing in improving the writing skills of English Tadris students.This research is a type of Classroom Action Research (CAR). This research was conducted on third-semester students of the English Tadris Study Program at IAIN Fattahul Muluk Papua. In this study, the researcher used total sampling, where the total number of semester III students was 19 people. However, the researcher only took data from 13 people because six students did not participate in the entire research cycle from start to finish. The results of this research are separated into two cycles. The researcher stopped conducting the research because the success criteria had been reached in cycle II. The results of the average score of student writing also increased in all aspects, viz content (2,8), organization (1,33), vocabulary (1,07), language use (0,93), and mechanics (1,2). For that, the researcher concluded that Creative Writing is able to improve the quality of writing. The majority of students gave a positive response to the application Creative Writing. Almost all students agree that Creative Writing is able to increase learning motivation, task completion, and social relations between fellow friends and lecturers.